2016
DOI: 10.1001/jamadermatol.2016.1005
|View full text |Cite
|
Sign up to set email alerts
|

Patient Preferences During Skin Cancer Screening Examination

Abstract: Discussion | This study provides a framework that facilitates meaningful clinical interpretation of the numerical mMASI score. The ranges for mMASI provided herein correspond to global levels of severity using the MSS. Such categorization in MSS levels can assist clinicians in interpreting clinical trial data, severity of disease, and response to treatment. The mMASI is a simple, reliable validated tool that is a modification of the most commonly used outcome measure for melasma. This user-friendly tool can no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…A previous study reported that about half of family practitioners or internists and approximately 20% of dermatologists do not routinely perform full-body skin examinations ( Oliveria et al, 2011 ). Other studies reported that women were more likely than men to report feeling embarrassed by a full-body skin examination and therefore may be less likely to have full-body skin examinations performed, especially by sex nonconcordant providers ( Federman et al, 2006 , Houston et al, 2016 , Rodriguez et al, 2007 ). Our findings highlight the need to closely examine the lower extremities of women and the head and neck of men, given that these are the most common sites of invasive cSCC.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that about half of family practitioners or internists and approximately 20% of dermatologists do not routinely perform full-body skin examinations ( Oliveria et al, 2011 ). Other studies reported that women were more likely than men to report feeling embarrassed by a full-body skin examination and therefore may be less likely to have full-body skin examinations performed, especially by sex nonconcordant providers ( Federman et al, 2006 , Houston et al, 2016 , Rodriguez et al, 2007 ). Our findings highlight the need to closely examine the lower extremities of women and the head and neck of men, given that these are the most common sites of invasive cSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Houston et al suggested that patients are more likely to agree to a total body skin examination when clinicians respect the patient's preference for the physician's gender 5 . Zikry et al 6 recommended, concerning the positioning of patients during these genital exams, that male genitalia can be examined with the patient standing and the physician seated on a stool in front of the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Imaging of the brain, chest, abdomen, and pelvis with chest radiograph, CT, or PET/CT scans every 4 to 12 months to screen for recurrent or metastatic disease should be considered in patients with a history of stage II to IV melanoma 11 . One recent study suggests that patients are more likely to agree to a total body skin examination when clinicians respect the patient's preferences for the physician's gender and degree of disrobement 13 . However, total body skin examination for skin cancer screening remains a controversial topic in the literature, and there is no national consensus for skin cancer screening in melanoma survivors.…”
Section: Discussionmentioning
confidence: 99%